ASHRAE greenguide the design, construction, and operation of sustainable buildings. (American Society of Heating, Refrigerating and Air-Conditioning Engineers Inc., 2010)
"The third edition of the ASHRAE GreenGuide features information for anyone charged with designing a sustainable building on a variety of green-design issues that should be considered when tasked with this type of project"--Provided by publisher.